Surgical iatrogenic infertility. - Pacheco Romero, José (2015)
It is the privilege of infertility obstetrician specializing in power use their intelligence and gift of creation and the art of his hands in the surgical correction of anatomical abnormalities of the reproductive tract. But, therefore its potential in the operating room and the significance of their decisions and actions, the surgeon of infertility can cause damage to your operating act to stop making steps for performing an incomplete or venture operation, - by mistake, ignorance or exaggerated autosuficiencia-, operate more than necessary. It's called iatrogenic damage to production or other problems with the medical services.